Successful manipulation of the quality and quantity of fat and carbohydrate consumed by free-living individuals using a food exchange model. - Moore, C; Gitau, R; Goff, L; Lewis, F; Griffin, MD; Chatfield, MD; Jebb, SA; Frost, G; Sanders, T; Griffin, B; Lovegrove, J (2009)
Our objective in this study was to develop and implement an effective intervention strategy to manipulate the amount and composition of dietary fat and carbohydrate (CHO) in free-living individuals in the RISCK study. The study was a randomized, controlled dietary intervention study that was conducted in 720 participants identified as higher risk for or with metabolic syndrome. All followed a 4-wk run-in reference diet [high saturated fatty acids (SF)/high glycemic index (GI)]. Volunteers were randomized to continue this diet for a further 24 wk or to 1 of 4 isoenergetic prescriptions [high monounsaturated fatty acids (MUFA)/high GI; high MUFA/low GI; low fat (LF)/high GI; and LF/low GI]. We developed a food exchange model to implement each diet. Dietary records and plasma phospholipid fatty acids were used to assess the effectiveness of the intervention strategy. Reported fat intake from the LF diets was significantly reduced to 28% of energy (%E) compared with 38%E from the HM and LF diets. SF intake was successfully decreased in the HM and LF diets to < or =10%E compared with 17%E in the reference diet (P = 0.001). Dietary MUFA in the HM diets was approximately 17%E, significantly higher than in the reference (12%E) and LF diets (10%E) (P = 0.001). Changes in plasma phospholipid fatty acids provided further evidence for the successful manipulation of fat intake. The GI of the HGI and LGI arms differed by approximately 9 points (P = 0.001). The food exchange model provided an effective dietary strategy for the design and implementation across multiple sites of 5 experimental diets with specific targets for the proportion of fat and CHO.